2023
DOI: 10.1021/acs.jcim.3c00396
|View full text |Cite
|
Sign up to set email alerts
|

Interpretable Molecular Property Predictions Using Marginalized Graph Kernels

Yan Xiang,
Yu-Hang Tang,
Guang Lin
et al.

Abstract: Marginalized graph kernels have shown competitive performance in molecular machine learning tasks but currently lack measures of interpretability, which are important to improve trust in the models, detect biases, and inform molecular optimization campaigns. We here conceive and implement two interpretability measures for Gaussian process regression using a marginalized graph kernel (GPR-MGK) to quantify (1) the contribution of specific training data to the prediction and (2) the contribution of specific nodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Interpretation approaches can be classified into two categories: global and local, corresponding to focusing on the prediction model itself and input instances, respectively. Various studies were reported on the local interpretation methods and associated applications, such as the identification of important substructures (atoms) in a molecule, compound optimization , and finding a potential artifact of a model . On the other hand, methods for global interpretations are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation approaches can be classified into two categories: global and local, corresponding to focusing on the prediction model itself and input instances, respectively. Various studies were reported on the local interpretation methods and associated applications, such as the identification of important substructures (atoms) in a molecule, compound optimization , and finding a potential artifact of a model . On the other hand, methods for global interpretations are limited.…”
Section: Introductionmentioning
confidence: 99%